Alkaloid content, antioxidant and cytotoxic activities of various parts of papaver somniferum - Sharopov, Farukh; Valiev, Abdujabbor; Gulmurodov, Isomiddin; Sobeh, Mansour; Satyal, Prabodh; Wink, Michael (Pharmaceutical chemistry journal, 2018)
Poppy (Papaver somniferum) is a traditional source of isoquinoline alkaloids, especially morphine, codeine and papaverine that exhibit a wide spectrum of therapeutic effects. Due to beneficial properties, poppy has been used by humankind for several thousand years and is still being used around the world. The present study was aimed to investigate alkaloid composition and biological activity of various parts of the plant (leaves, stems, roots, capsules, flowers, seeds) in an ornamental variety of P. somniferum. The alkaloid content rangedwithin 0.16 - 6.5 mg/g fresh weight of raw plant material. The major components of the alkaloid fraction were papaverine (37.7 - 2062.9 μg/g), codeine (7.4 - 1280.5 μg/g) and morphine (3.25 - 929.3 μg/g). The P. somniferum alkaloid extract produced a strong antioxidant effect, which was evaluated using the radical-scavenging DPPH, ABTS and FRAP assays. The antioxidant properties were characterized by IC50 values ranging within 35.1 - 157.6 μg/mL for DPPH radical and 138.5 - 306.3 μg/mL for ABTS∙•+ radical scavenging. The ferric reducing antioxidant power (FRAP) values varied from 59.75 to 1348.71 mM FeSO4/g extract. The alkaloid extract was active against all human tumor cell lines studied (HeLa, Caco-2, MCF-7, CCRF-CEM and CEM/ADR 5000). The methanol extract exhibited a pronounced cytotoxicity against most of cancer cell lines studied, especially those with a low expression of ABC transporters.
Gesehen am 01.10.2019